Preservice teachers’ science learning and self-efficacy to teach with robotics-based activities: Investigating a scaffolded and a self-guided approach - Jaipal-Jamani, Kamini (Frontiers in Education, 2023)
Makerspace is being viewed as a viable pedagogical strategy for STEM learning because makers (e.g., hackers and tinkerers) in informal spaces, use many practices common to the STEM disciplines such as engineering design. There is therefore a need for empirical evidence about the effectiveness of makerspaces in formal educational settings to promote curriculum learning outcomes and to support teaching practice. The study reported investigated the effectiveness of a makerspace robotics intervention and a scaffolded, inquiry robotics intervention in relation to two variables: pre-service teachers’ knowledge of science concepts (e.g., gears) and their self-efficacy to teach with robotics. A quasi-experimental, pre-post intervention study was implemented with two non-equivalent groups of elementary preservice teachers (PSTs) in a Bachelor of Education program. PSTs in the maker intervention class engaged with robotics kits in an open-ended way in the library. PSTs in the scaffolded, inquiry intervention class were guided through the activity by the author with instructional scaffolds. Both groups used LEGO WeDo robotics kits. IBM SPSS Statistics 25 was used to analyze the data. Normality tests, one-way ANCOVA with pretest as covariate, independent samples t-tests, paired samples t-tests and effect sizes were computed. The findings were statistically significant for relationships between each intervention type and gains in science knowledge. However, the effect size for the scaffolded inquiry intervention was higher indicating that the scaffolded inquiry intervention caused bigger gains in preservice teachers’ knowledge. With respect to self-efficacy, the scaffolded intervention showed significant gains for all four self-efficacy items whereas the maker intervention had no significant effect on preservice teachers’ self-efficacy to teach science with robotics. The study provides empirical evidence that while a maker approach did cause some gains in knowledge, it was not effective at developing preservice teachers’ self-efficacy to teach with robotics. These results indicate that a scaffolded inquiry robotics approach, modelled for and experienced by pre-service teachers, is more effective than the maker approach for the learning of STEM curricular concepts and for developing the confidence of preservice teachers to integrate robotics in practice; the latter contributing to robotics adoption in K-12 schools and development of STEM knowledge and skills